2023
DOI: 10.1002/adma.202300830
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Latent Bases in Dynamic Covalent Polymer Networks and their Emerging Applications

Abstract: A novel strategy allowing temporal control of dynamic bond exchange in covalently crosslinked polymer networks via latent transesterification catalysts is introduced. Obtained by a straightforward air‐ and water‐tolerant synthesis, the latent catalyst is designed for an irreversible temperature‐mediated release of a strong organic base. Its long‐term inactivity at temperatures below 50 °C provides the unique opportunity to equip dynamic covalent networks with creep resistance and high bond‐exchange rates, once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
(113 reference statements)
2
20
0
1
Order By: Relevance
“…S4b, ESI †). 10,18 On the obtained covalently cross-linked 1 mm thick polymer sample, stress relaxation measurements were performed in the linear viscoelastic range of the material at a deformation of 3%. Amplitude sweep experiments are shown in Fig.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
See 2 more Smart Citations
“…S4b, ESI †). 10,18 On the obtained covalently cross-linked 1 mm thick polymer sample, stress relaxation measurements were performed in the linear viscoelastic range of the material at a deformation of 3%. Amplitude sweep experiments are shown in Fig.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…8 Within subsequent studies, we combined the holistic idea of latent catalysis of dynamic transesterification in vitrimer systems with digital light processing (DLP) 3D printing. [9][10][11] Whereas thermally latent catalysts can be used regardless of the absorption characteristics of the photoinitiator, photolatent catalysts require an (at least) sequence-dependent wavelength-orthogonality. 10 To achieve this fundamental prerequisite, the emission range of the light source used for DLP 3D printing must be adequately separated from the excitation window of the photolatent catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, quaternary ammonium salts exhibit distinct catalytic behavior by displaying basic properties upon liberation of a tertiary amine. , Originally employed to achieve temporal and thermal control of the curing reaction processes of diverse formulations, and more recently to enhance the durability and stability of PU adhesives, this type of organocatalyst has garnered attention in polymer chemistry due to their facile and scalable synthesis, making their use suitable for industrial applications. More recently, this concept has been extended to trigger the dynamic exchange in CANs: Schlögl and co-workers showed the promotion of transesterification reactions by the thermal activation of a latent base, 1,5,7-triazabicyclo[4.4.0]­dec-5-enylcyanoacetate (TBD-CA), in a cross-linked thiol–ene polymer network . The organic salt dissociation occurred at 130 °C, which also triggered the decarboxylation of the acid, leading to the irreversible release of the catalytic TBD.…”
mentioning
confidence: 99%
“…More recently, this concept has been extended to trigger the dynamic exchange in CANs: Schlogl and co-workers showed the promotion of transesterification reactions by the thermal activation of a latent base, 1,5,7-triazabicyclo[4.4.0]dec-5-enylcyanoacetate (TBD-CA), in a cross-linked thiol−ene polymer network. 23 The organic salt dissociation occurred at 130 °C, which also triggered the decarboxylation of the acid, leading to the irreversible release of the catalytic TBD. This group has also shown that a latent catalyst activation can be achieved by light.…”
mentioning
confidence: 99%